Using interactive videos in general practice to inform patients about treatment choices: a pilot study. - Shepperd, S; Coulter, A; Farmer, A (1995)
Our objective was to assess the acceptability of using an interactive video system in a general practice setting to inform patients about treatment choices. A descriptive cohort study was carried out in eight general practices in Oxfordshire. Fifty-four patients with mild hypertension and 29 with benign prostatic hypertrophy were studied. Patients' views of the video, treatment preference, level of involvement in treatment decision and satisfaction with decision-making process and GPs' views of the effect of the video on subsequent consultations were measured. Both patients and GPs reported favourable impressions of the interactive video system: 71% of patients said it definitely helped with their treatment decision; GPs said they found the video helpful in 82% of cases. The results of this pilot study were sufficiently encouraging to indicate the need for a randomized controlled trial to evaluate the impact of the video on the doctor-patient relationship, on subsequent treatment decisions and on health outcomes and patients' well-being.